Intergenerational Bonds The Contributions of Older Adults to Young Children's Lives - Renck Jalongo, Mary.; Crawford, Patricia A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This book studies the many different ways in which the lives of the first, third, and fourth generations intersect and the reciprocal benefits that can accrue from establishing positive intergenerational bonds. The unifying feature across the chapters is that the authors view these relationships as a powerful influence on Quality of Life (QoL). The book takes the stance that older adults figure prominently in the QoL of young children, with the latter group defined here as ranging in age from infancy up to and including eight years of age. It examines how bonds with older adults can affect young children$1 (Bs functioning across developmental domains$1 (Bphysical, emotional, social, and cognitive. It addresses questions of importance to those who have a commitment to the very young such as: (3z(BWhat benefits can young children derive from positive bonds with older adults?(3y(B, (3z(BHow do young children understand the aging process and develop respect for the elderly?(3y(B, (3z(BHow can published research be used to guide both informal and formal interactions between the older generation and the newest one?(3y (Band, finally, (3z(BHow can various stakeholders such as professionals, families, organizations, and communities collaborate to enrich and enlarge the kind and amount of support that older adults provide to the very young child?(3y(B.s
Foreword -- Preface -- Part One: Young children's concepts of aging -- Part Two: Young children and older extended family members -- Part Three: Promoting positive intergenerational relationships in communities -- Part Four: Literacy and learning.
Keywords: Early childhood education; Clinical psychology; Internal medicine; Cognitive psychology; Social structure; Equality; Early Childhood Education; Clinical Psychology; Internal Medicine; Cognitive Psychology; Social Structure